Size magnification as a complement to cosmic shear - Casaponsa, B; Heavens, A; Kitching, T; Miller, L; Barreiro, R; Martinez-Gonzalez, E (2013)
We investigate the extent to which cosmic size magnification may be used to complement cosmic shear in weak gravitational lensing surveys, with a view to obtaining high-precision estimates of cosmological parameters. Using simulated galaxy images, we find that unbiased estimation of the convergence field is possible using galaxies with angular sizes larger than the point spread function (PSF) and signal-to-noise ratio in excess of 10. The statistical power is similar to, but not quite as good as, cosmic shear, and it is subject to different systematic effects. Application to ground-based data will be challenging, with relatively large empirical corrections required to account for the fact that many galaxiesare smaller than the PSF, but for space-based data with 0.1-0.2 arcsec resolution, the size distribution of galaxies brighter than i≃24 is almost ideal for accurate estimation of cosmic size magnification. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.